Comportamento de elementos pré-moldados de concreto com ligações semi-rígidas - Souza, Abner Soares de (Universidade Federal de São Carlos, 2006)
The behaviour of reinforced concrete precast beams is strongly influenced by the flexural stiffness of its beam-column connections, wherein there is interdependence between the nonlinearity of the moment-curvature relationship along the beam and the non-linearity of the moment-rotation relationship of the beam-column connections. In most of the existing researches on semi-rigid connections in precast structures, the main focus lays on the characterization of the flexural stiffness by performing experimental tests on isolated models of beam-column connections instead of tests on sub-frames, comprising beam and connections. In this research an experimental procedure was developed, wherein different theoretical equations based on the fixity factor of the connections were combined, allowing the integration between the stiffness of the reinforced concrete beam with the flexural stiffness of the beam-column connections. Therefore, by using this procedure it was possible to evaluate the semi-rigid behaviour of the beam-column connection, highlighting the possibility of carrying out just one test for the precast beam with its connections. The analyses of the experimental results indicate that the studied connection was capable of absorbing around 53% of the elastic beam-end moment at the ULS, compared with the situation of a full restrained connector, implying the increase of 170% of the positive mid-span moment of the beam. This level of semi-rigid behaviour for the beam-column connection can affect the global stability of skeletal precast concrete structures with more than five storeys in height. For this reason, the present research shows the need for further studies with the purpose of enhancing the analysis and the design of precast concrete structures for multi-storey buildings.
Behaviour of concrete precast elements with semi-rigid connections
Keywords: Concreto pré-moldado; Ligações semi-rígidas; Ligações viga-pilar; Rigidez à flexão; Beam-column connections; Semi-rigid connections; Precast beams; Flexural stiffness; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL